Concurrent occurrence of a bovine viral diarrhoea virus type-1 (BVDV-1) infection and Trueperella pyogenes bronchopneumonia in a calf - Eroksuz, Yesari; Abayli, Hasan; Yerlikaya, Zeynep; Incili, Canan Akdeniz; Karabulut, Burak; Eroksuz, Hatice (Czech Academy Agricultural Sciences, 2021)
The concurrent occurrence of a bovine viral diarrhoea virus type-1 infection and necrotising-suppurative bronchopneumonia due to Trueperella pyogenes was diagnosed in a 4-month-old male calf. The pulmonary lesions were characterised by necro-suppurative bronchopneumonia with intralesional gram-positive microorganisms. The reverse transcription polymerase chain reaction (RT-PCR) and matrix-assisted laser desorption ionisation time-of-flight mass spectrometry analysis (MALDI-TOF MS) also indicated the presence of BVDV type-1 and Trueperella pyogenes agents, respectively. A positive immunoreaction to the BVDV was present in the vascular walls in the lungs, hepatocytes, lymphoid cells in the spleen and lymph nodes, and neurons in the brain. With this case study, the two infections were, to the best of our knowledge, reported concurrently for the first time. It can be assumed that a subclinical BVDV infection might contribute to the occurrence of Trueperella pyogenes infections in calves.
Keywords: animal diseases; bovine; PCR; ruminant